2019
DOI: 10.1103/physrevaccelbeams.22.123402
|View full text |Cite
|
Sign up to set email alerts
|

High power conditioning and benchmarking of planar nitrogen-incorporated ultrananocrystalline diamond field emission electron source

Abstract: Planar nitrogen-incorporated ultrananocrystalline diamond, (N)UNCD, has emerged as a unique field emission source attractive for accelerator applications because of its capability to generate high charge beam and handle moderate vacuum conditions. Most importantly, (N)UNCD sources are simple to produce: conventional high aspect ratio isolated emitters are not required to be formed on the surface, and the actual emitter surface roughness is on the order of only 100 nm. Careful reliability assessment of (N)UNCD … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(93 reference statements)
0
16
0
Order By: Relevance
“…The most remarkable and surprising result was that the emission threshold gradient was as low as 0.57 MV/m. Even though a turn-on field as low as 0.5 MV/m was reported once for nitrogen doped microcrystalline diamond in dc regime [5], in our previous dc and rf studies [3,6] lowest turn-on dc field and rf gradient were 2.5 and 8 MV/m, respectively, for the (N)UNCD emitters synthesized under same conditions. In case of the latest rf measurements [3], the rf system was limited in terms of lowest power (yielding gradient on the cathode), and pulse length and duty cycle (yielding total emitted charge per second) available from the L-band klystron.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The most remarkable and surprising result was that the emission threshold gradient was as low as 0.57 MV/m. Even though a turn-on field as low as 0.5 MV/m was reported once for nitrogen doped microcrystalline diamond in dc regime [5], in our previous dc and rf studies [3,6] lowest turn-on dc field and rf gradient were 2.5 and 8 MV/m, respectively, for the (N)UNCD emitters synthesized under same conditions. In case of the latest rf measurements [3], the rf system was limited in terms of lowest power (yielding gradient on the cathode), and pulse length and duty cycle (yielding total emitted charge per second) available from the L-band klystron.…”
mentioning
confidence: 68%
“…Electron emission from the (N)UNCD planar surface with excellent emittance, energy spread, and stability were confirmed. rf pulse currents of ∼1-100 mA were achieved [1][2][3]. At high rep-rate/CW operation, such pulse current range serves as an average current estimate for SRF applications, given that field emission is a quantum tunneling effect (meaning that similar currents are expected between 2 K and room temperature).…”
mentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6] have convincingly demonstrated that the electron emission from a large surface area field emission cathode placed in a macroscopic electric field E is not uniform. The emission area is only a small portion of the total surface area of a cathode since most of the emission is confined to a small number of emission spots randomly distributed over the cathode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Second is fundamental: only a properly established j-E (and not I-V ) relationship can be used to define the validity range of a classical Fowler-Nordheim (FN) emission and clarify the role of other mechanisms that could cause deviation from the FN emission, i.e. cause non-conventional behavior that is being observed across a large body of experimental work [1][2][3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Cathode fabrication is based on standard silicon wafer techniques, allowing the production of arrays with nearly arbitrary geometric shapes. In this article, we present initial results from the two dense triangular DFEA cathodes that were tested in the RF gun at the Argonne Cathode Test-Stand (ACT) Facility at ANL [12]- [14], as well as initial simulations of tip-to-tip shielding. Results from the sparse array tests, which successfully demonstrated production and transport of a patterned beam from a field-emission cathode in an RF gun, along with initial estimates of the per-tip current and emission area, are reported elsewhere [18].…”
mentioning
confidence: 99%